2004
DOI: 10.1162/089892904322926791
|View full text |Cite
|
Sign up to set email alerts
|

Reward-related Reversal Learning after Surgical Excisions in Orbito-frontal or Dorsolateral Prefrontal Cortex in Humans

Abstract: Neurophysiological studies in primates and neuroimaging studies in humans suggest that the orbito-frontal cortex is involved in representing the reward value of stimuli and in the rapid learning and relearning of associations between visual stimuli and rewarding or punishing outcomes. In the present study, we tested patients with circumscribed surgical lesions in different regions of the frontal lobe on a new visual discrimination reversal test, which, in an fMRI study (O'Doherty, Kringelbach, Rolls, Hornak, &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
361
3
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 538 publications
(402 citation statements)
references
References 46 publications
34
361
3
4
Order By: Relevance
“…By contrast, reversal learning may depend specifically on function of the orbitofrontal cortex, as suggested in humans (Hornak et al 2004;Rolls et al 1994), non-human primates (Clarke et al 2004;Dias et al 1996), and more recently in rats (McAlonan and Brown 2003). Thus, it appears that different types of chronic stress may have different effects on cognitive flexibility, dependent upon distinct subregions of prefrontal cortex, and potentially involving dysregulation of different monoaminergic systems.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, reversal learning may depend specifically on function of the orbitofrontal cortex, as suggested in humans (Hornak et al 2004;Rolls et al 1994), non-human primates (Clarke et al 2004;Dias et al 1996), and more recently in rats (McAlonan and Brown 2003). Thus, it appears that different types of chronic stress may have different effects on cognitive flexibility, dependent upon distinct subregions of prefrontal cortex, and potentially involving dysregulation of different monoaminergic systems.…”
Section: Discussionmentioning
confidence: 99%
“…where A is now not rewarded and B is rewarded e.g. (Butter, 1969;Chudasama & Robbins, 2003;Dias, Robbins, & Roberts, 1996;Hornak et al, 2004;Iversen & Mishkin, 1970). A possible account for the discrepancy is that reversal is normally a faster process than initial acquisition because the task relevant information becomes evident to the subject following acquisition (Kruschke, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies demonstrated involvement of the DMPFC in the cognitive regulation of emotion processing [Beauregard et al, 2001;Blood and Zatorre, 2001;Hornak et al, 2004;Kalisch et al, 2006;Ochsner et al, 2002Ochsner et al, , 2004Phillips et al, 2003;Price, 1999]. Phan et al [2002] therefore conclude that the DMPFC is engaged in implicit cognitive aspects of emotion processing that are common across emotional tasks.…”
Section: Introductionmentioning
confidence: 92%